Tumour-associated lymphangiogenesis in conjunctival malignant melanoma. Issue 11 (23rd July 2009) - Zimmermann, P; Dietrich, T; Bock, F; Horn, F K; Hofmann-Rummelt, C; Kruse, F E; Cursiefen, C
Abstract : Background: To evaluate whether tumour-associated lymphangiogenesis, that is the formation of new lymphatic vessels (LVs) induced by a tumour, occurs in and around conjunctival malignant melanoma (MM). Methods: Clinical files and conjunctival specimens of 20 patients with histologically diagnosed conjunctival MM were analysed. Sections were stained with LYVE-1 and podoplanin antibodies as specific lymphatic endothelial markers and Ki67 as proliferation marker. The tumour area and the area covered by LV (LVA), LV number (LVN) and LV density (LVD) were measured within the tumour and in the peritumoural area in digital images of the specimen. The LV results were correlated with the histopathological characteristics, tumour location, recurrence rate, mitomycin C therapy and presence of metastases. Results: LVs were detected in all specimens within the tumour and peritumourally. Significantly more Ki67 + proliferating lymphatic endothelial cells were detected in the tumour and in the peritumoural tissue up to 300 μm compared with the surrounding normal conjunctiva (>300 μm distance). There was a slightly positive correlation between the tumour size and the LVN and LVA in the 50 μm zone adjacent to the tumour. We did not find any significant correlations between LVs and histopathological and clinical characteristics (location, shape, relapses, metastases), possibly due to the small sample sizes. Non-limbal tumours with involvement of tarsus or fornix showed a tendency towards a higher LVD compared with limbal tumours. Conclusion: Conjunctival MMs display tumour-associated LV within and around the tumour. The MM seems to induce lymphangiogenesis not only in the tumour, but also in its proximity.